Freshly characterization and storability of mini head lettuces at optimal and abusive temperatures - Viacava, Gabriela Elena; Ponce, Alejandra Graciela; Goyeneche, Rosario; Carrozzi, Liliana; Yommi, Alejandra Karina; Roura, Sara Ines (Sage Publications, 2019)
Selection of lettuce varieties less sensitive to quality deterioration and more tolerant to abusive temperatures during handling, transportation, and storage is essential to minimize economical and quality losses that affect both producers and consumers. This work was focused on the quality changes of four baby head lettuces (Lactuca sativa L.), two butter (red and green) and two oak-leaf (red and green) types, during storage at 0 ℃ and 10 ℃ for 10 days. Lettuce quality was determined by measuring bioactive content (ascorbic acid, total phenolics), physicochemical (total chlorophyll, browning potential), and microbiological indices. At harvest, red varieties presented lower browning potential and higher bioactive compounds but no differences were observed in microbial populations. During storage, ascorbic acid underwent first order degradation for all varieties, with a degradation rate at 10 ℃ twice faster than at 0 ℃. At 0 ℃, only the red oak-leaf lettuce exhibited chlorophyll degradation, while at 10 ℃ all varieties presented degradation. No changes were observed in total phenolics and browning potential of butter lettuces during storage at both temperatures. Microbial population counts were significant affected by the storage temperature. Red butter baby lettuce presented slightly better bioactive content and microbiological characteristics and then better storability.